Receptor Pre-Clustering and T cell Responses: Insights into Molecular Mechanisms - Castro, Mario; van Santen, Hisse M.; Férez, María; Alarcón, Balbino; Lythe, Grant; Molina-París, Carmen (Frontiers in Immunology, 2014)
T~cell activation, initiated by T~cell receptor (TCR) mediated recognition of pathogen derived peptides presented by major histocompatibility complex class I or II molecules (pMHC), shows exquisite specificity and sensitivity, even though the TCR-pMHC binding interaction is of low affinity. Recent experimental work suggests that TCR pre-clustering may be a mechanism via which T~cells can achieve such high sensitivity. The unresolved stoichiometry of the TCR makes TCR-pMHC binding and TCR triggering an open question. We formulate a mathematical model to characterise the pre-clustering of T~cell receptors (TCRs) on the surface of T~cells, motivated by the experimentally-observed distribution of TCR clusters on the surface of naive and memory T~cells. We extend a recently-introduced stochastic criterion to compute the timescales of T~cell responses, assuming that ligand-induced cross-linked TCR is the minimum signalling unit. We derive an approximate formula for the mean time to signal initiation. Our results show that pre-clustering reduces the mean activation time. However, additional mechanisms favouring the existence of clusters are required to explain the difference between naive and memory T~cell responses. We discuss the biological implications of our results, and both the compatibility and complementarity of our approach with other existing mathematical models.